Use of Mini-Implant Anchorage For Second Molar Mesialization: Comprehensive Approach For Treatment Efficiency Analysis - Oleh Rivis; Anatoliy Potapchuk; Myroslav Goncharuk-Khomyn; Anatoliy Bokoch (Association of Support to Oral Health Research (APESB), 2022)
Objective: To approbate the complex approach for assessment of second molar mesialization outcomes with the use of orthodontic mini-implants. Material and Methods: The sample consisted of 62 patients, divided into study (n=32) and control group (n=30). Mesialization procedure in the study group was conducted with the use of braces system and orthodontic mini-implants as additional anchorage devices, while in control group mesialization was provided only with the use of the brace system. Dynamic registration of bone level changes and the entire range of tooth movement were carried out on digital orthopantomograms obtained with the use of Planmeca ProMax 2D. Results: Findings of orthopantomographic (OPG) analysis have shown that cases of second molar mesialization with the use of mini-implants as temporary anchorage characterized with more stable conditions of bone levels around displaced teeth compare to cases, where mesialization was provided only with the use of braces systems without  any  additional anchorage. The terms of treatment in the study group with the use of dental mini-implants as the anchorage was reduced by 8.8 ± 0.12 months compared to the control group (p<0.05). Conclusion: The use of orthodontic mini- implants as anchorage constructions during  the mesialization  of the mandibular second molars contributes to the reduction of treatment duration and support the more prognostic movement of teeth, that does not provoke significant pathological changes in the levels of the surrounded alveolar ridge and minimize the risk of associated periodontal complication occurrence.